Rating Bonds Before Moody’s: 1886-1893 - Thies, Clifford F. (Journal of Accounting and Finance, 2023)
This paper is the first in a series examining the credit quality of an evolving sample of seasoned, medium to high-grade, long-term railroad bonds during the late 19th and early 20th Centuries. The paper develops a simple model capable of pricing these bonds and assembles the requisite financial statement and market data needed to calibrate the model. The exercise demonstrates that these bonds were priced according to the financial strength of their issuer and their priority of claim (and modified by other factors, many of which are interesting in themselves). These findings suggest that these bonds can be rated from information available in real-time before Moody’s innovation of bond ratings in 1909.